Does Work-life Balance Predict Psychological Well-being among Federal Medical Doctors and Nurses in Southeast Nigeria? - Onwuamaegbu, Promise O.; Sydney-Agbor, Ngozi N. (Journal of Psychology and Allied Disciplines, 2023)
The need to ascertain the impact of work-life balance (WLB) among doctors and nurses is imperative considering their ever-increasing work demands. Thus, the study seeks to ascertain if work interference with personal life (WIPL), personal life interference with work (PLIW), work/personal life enhancement (W/PLE), and if overall WLB will positively predict psychological well-being. The study equally examines whether doctors and nurses will significantly differ in their psychological well-being. To achieve this, three hundred and four doctors and nurses drawn from three Federal Hospitals through the cross-sectional survey research design in Southeast Nigeria. They comprised one hundred and eleven (111) doctors and one hundred and ninety-three (193) nurses between the ages of 30 –58 (M = 44.20, SD = 6.28). Results indicate that WIPL, PLIW, W/PLE, and overall WLB do not predict psychological well-being However, doctors are found to differ significantly from Nurses in their psychological well-being It was recommended inter alia that wellness programmes aimed at improving the psychological well-being of doctors and more especially nurses should be routinely done.